Sex and educational attainment differences in HPV knowledge and vaccination awareness among unvaccinated-sexually active adults in Puerto Rico - Maira A. Castañeda-Avila; Carla J. Oramas Sepúlveda; Cynthia M. Pérez; Jeslie M. Ramos-Cartagena; Kimil Acosta Pagán; Josué Pérez-Santiago; Filipa Godoy-Vitorino; Ana P. Ortiz (Taylor & Francis Group, 2022)
Human papillomavirus (HPV) knowledge and HPV vaccination uptake remain suboptimal. We assessed sex and educational attainment differences in HPV knowledge and vaccine awareness. Data from a cross-sectional study (2018-2021) in Puerto Rico among adults aged 21-49 was analyzed (n = 278). Adequate knowledge was defined as a score of ≥70% of correct responses on a 13-item knowledge scale. Multivariable logistic regression was used to assess the association of sex (men vs. women) and education (high school or less vs. more than high school) categories with adequate HPV knowledge and vaccine awareness. Adequate HPV knowledge was higher among women (53%) and men (46%) with more than high school and was lower among women (46%) and men (27%) with high school or less. For HPV vaccine awareness, similar results were observed. Women (OR = 3.0 ; 95%CI = 1.4-6.2) and men (OR = 2.3 , 95%CI = 1.1-4.8) with more than high school and women with high school or less (OR = 2.3 , 95%CI = 1.0-5.2) were more likely to have adequate HPV vaccine knowledge than men with high-school or less education. Heightened HPV vaccine awareness was also seen among more educated women and men and women with similar lower education when compared to men with ≤ high school. Men and individuals with lower educational attainment were more likely to have inadequate HPV knowledge and vaccine awareness. HPV vaccine-oriented educational interventions should target these high-risk groups.